Discovery of Metacrangonyx in inland groundwaters of Oman (Amphipoda: Gammaridea: Metacrangonyctidae) - Jaume, Damià; Vonk, Ronald (Zootaxa, 2012)
A new species of metacrangonyctid amphipod crustacean is described from the Salalah coastal plain aquifer in south-western Oman. This is the easternmost record of the group, with representatives previously thought to span from Hispaniola in the Caribbean to the Sinai Peninsula in Egypt. Metacrangonyx dhofarensis sp. nov. is unique among metacrangonyctids in the display of a sexually dimorphic armature on pereiopod IV. In addition, its hypertrophied coxal plate IV, reduced plates I-III, coxal plate VII lacking anteroventral lobe, and telson longer than broad are also distinctive. The same holds for the proximal segment of peduncle of antennule, provided with two hypertrophied robust setae on dorsolateral margin. The mandibles of the new species are devoid of palp, a feature shared only with Metacrangonyx antennatus Messouli, El Alami, Coineau & Boutin, 2008. The presence of metacrangonyctids on the coasts of the Arabian Peninsula is probably the result of a vicariant event rather than of an episode of trans-Arabian continental dispersal by a Middle East ancestor. This is in accord with the presumed marine origin of the family and with the existence of a shallow water marine continuum between the current south-western Omani coast and the peri-Mediterranean area -where most species of metacrangonyctids are located - until approximately 16 Ma.